A novel approach to treating mirror hand deformity: a case report of functional thumb reconstruction using a palmar incision design - Shi, Yufeng; Hu, Ruibin; Shen, Hangchong; Wang, Xin; Zhou, Danya (Frontiers in Surgery, 2025)
Congenital anomalies of the hand and forearm present a complex challenge in plastic and pediatric surgery. We present the case of a 13-month-old child with a congenital left mirror deformity, characterized by the presence of eight digits and two ulnae exhibiting near-perfect bilateral symmetry. A novel palmar-based incision design was employed for the corrective and functional reconstruction of the left hand, which may serve as a reference for the surgical management of similar conditions. Preoperatively, the radial-side middle finger demonstrated palmar opposition against the ulnar aspect of the palm. The surgical procedure included resection of the radial-sided index, ring, and little fingers, along with pollicization of the middle finger. Functional reconstruction of the neothumb involved restoring adduction and abduction using preserved native anatomical structures. Following comprehensive clinical and imaging evaluations, the patient underwent successful surgical treatment. Postoperatively, substantial improvements were observed in both hand morphology and grasping function. Through our novel palmar incision approach, we effectively reconstructed thumb opposition and adduction while preserving intrinsic hand musculature and achieving optimal scar concealment. In managing mirror hand deformities, meticulous selection of the most dominant digit for thumb reconstruction remains crucial. At the initial surgical stage, osteotomy of the selected digit was performed to enhance its morphological similarity to a normal thumb.